Effects of anti-browning pretreatments, heat treatment and storage temperature on sugarcane (saccharum officinarum L.) juice quality - Abaya, Maria Nielita N. (College of Home Economics, University of the Philippines Diliman, 2012)
The study aimed to investigate the effects of anti-browning pretreatments, heat treatment, and storage temperature on the physicochemical, microbiological and sensory quality of sugarcane juice. Sugarcane juice samples were subjected to six different anti-browning pretreatments, including blanching (80oC for 5 min) and addition of 500 ppm ascorbic acid and 1000 ppm sodium metabisulfite. The physicochemical parameters evaluated were color, browning index, pH, total soluble solids, titrable acidity, PPO activity, total phenolic content and chlorophyll content. . Results showed that blanching (80oC for 5 min) the stalks and addition of 500 ppm ascorbic acid to the juice can significantly (p <0.05) reduce browning by inhibiting PPO activity. Sugarcane juice samples extracted from blanched stalks and added with 500 ppm ascorbic acid were then heated at different temperatures (70oC, 80oC and 90oC) for 10 min and the physicochemical, microbiological, and sensory properties were evaluated. Heat treatment at 70oC significantly reduced (p <0.05) the microbial content of the juice and caused minimal effects on the juice's physicochemical and sensory quality. Changes in the physicochemical, microbiological, and sensory quality of the pretreated and heat treated sugarcane juice stored at room (28oC) and low temperatures (10oC) were monitored. Low temperature storage was able to significantly (p <0.05) slow down the undesirable changes in the overall quality of the juice, wherein only slight variation in the color values, browning index, pH, titrable acidity, microbial counts and sensory properties occured during two weeks of storage.